MORALITY IN ASIAN FOLKTALES (A COMPARATIVE STUDY) - Septiani, Fika Indah; Nahdhiyah, Nahdhiyah (Elite : English and Literature Journal, 2016)
This article aims at finding the types of moral and uncovering life messages of five folktales from Asia for children. The folktales are King Vikramaditya (India), Visu the woodsman and Old priest (Japan), Makatho (Myarmar), The Golden Cucumber (Indonesia), and A lazy boy (Korea). Content analysis technique is used in analyzing data which coding sheet as instrument is used in coding process. Finding types and messages of the folktales based on Neiman's theory. This article finds there are thirty-one data of moral aspects which classify into four types of moral: religious morality, individual morality, natural morality and social morality. Each folktale in each country has different story and different moral message. The recommendation of this research is due to parent and teacher for being more selective in choosing folktale for children or student.